Understanding Bullying in an Affluent, Academically Rigorous U.S. High School: A Grounded Theory Analysis - Allen, Kathleen P. (Journal of human behavior in the social environment, 2013)
Students and staff members from a U.S. high school were asked to discuss their understanding of bullying within the context of their school social environment. Findings from the grounded theory analysis suggest that understandings of bullying are socially constructed and that how bullying is understood is influenced by context and by the negotiation of identity within that context. Furthermore, subjects focused on drama, a form of social interaction considered far more common than bullying. Findings suggest that research on bullying may benefit from shifting its emphasis on defining bullying and establishing prevalence, to exploring youths' contextual and developmental perspectives.